A Century of Circulation: The Return of the Smithsonian Institution's Duplicate Anthropological Specimens. (September 2014) - Nichols, Catherine A.
Abstract For nearly a century, the Smithsonian Institution permanently distributed "duplicate specimens" from its museum collections to public educational institutions. In 1903 and 1905, shipments of anthropological material were sent to the Jackson Free Library in Jackson, Tennessee, to be used as educational tools. Using a biographical methodology, I trace the movement of objects from the Smithsonian Institution to this small library, their uses in Jackson, and their eventual return to the National Museum of Natural History in 2007. Through this case study, I argue that, while preservation is a key function of the museum, the determination of which objects museums keep is contingent on the discursive formations and value systems of museums, anthropologists, and curators. [deaccessioning, Smithsonian Institution, collections management, history of anthropology]